Significance of mental health legislation for successful primary care for mental health and community mental health services: A review - Getinet Ayano (AOSIS, 2018)
Background: Mental health legislation (MHL) is required to ensure a regulatory framework for mental health services and other providers of treatment and care, and to ensure that the public and people with a mental illness are afforded protection from the often-devastating consequences of mental illness. Aims: To provide an overview of evidence on the significance of MHL for successful primary care for mental health and community mental health services Method: A qualitative review of the literature on the significance of MHL for successful primary care for mental health and community mental health services was conducted. Results: In many countries, especially in those who have no MHL, people do not have access to basic mental health care and treatment they require. One of the major aims of MHL is that all people with mental disorders should be provided with treatment based on the integration of mental health care services into the primary healthcare (PHC). In addition, MHL plays a crucial role in community integration of persons with mental disorders, the provision of care of high quality, the improvement of access to care at community level. Community-based mental health care further improves access to mental healthcare within the city, to have better health and mental health outcomes, and better quality of life, increase acceptability, reduce associated social stigma and human rights abuse, prevent chronicity and physical health comorbidity will likely to be detected early and managed. Conclusion: Mental health legislation plays a crucial role in community integration of persons with mental disorders, integration of mental health at primary health care, the provision of care of high quality and the improvement of access to care at community level. It is vital and essential to have MHL for every country.